Dental workforce shortage in Florida and access to oral health care for patients with Autism Spectrum Disorder and special needs: a narrative review and strategic health management model - Paulo Vinicius de Oliveira Bastos; Érica Cristina dos Santos; Rafael Rudimar Holler Peres; Maurício Santos Souza; Ricardo Ramaldes de Souza; Pâmela Gutheil Diesel; Angelo Zottele Piasentin; Regina Sanglard de Souza (South Florida Journal of Environmental and Animal Science, 2026)
The rising prevalence of Autism Spectrum Disorder (ASD) in the United States has outpaced the growth of a dental workforce specifically trained to provide care for this population, a mismatch that is compounded, in Florida, by a broader and officially documented shortage of dental practitioners. This narrative review examines the intersection between Florida's HRSA-designated dental workforce shortage and the oral health access gap experienced by individuals with ASD and other special needs, drawing on official data from the Health Resources and Services Administration (HRSA), the Florida Department of Health, the Centers for Disease Control and Prevention (CDC), and the Centers for Medicare & Medicaid Services (CMS), together with peer-reviewed literature on barriers to dental care in ASD populations. As of January 2026, Florida required 1,271 additional dentists to eliminate its dental Health Professional Shortage Area (HPSA) designations. Nationally, ASD prevalence among 8-year-old children rose from 1 in 150 in 2000 to 1 in 31 in 2022, with Florida consistently ranking among the states with the highest reported prevalence. The dental literature identifies a distinct, additional shortage of clinicians trained in special care dentistry, attributed largely to insufficient predoctoral and postdoctoral curriculum exposure, alongside well-documented sensory, communication, and behavioral barriers to care. These findings are synthesized into a concrete strategic model for a sensory-adapted, ASD-focused dental clinic. The study's limitations and directions for future empirical research are discussed.